Lessons in Building Professional Networks During Times of Crisis and their Impact on Nuclear Security Culture: The Case of the Black Sea Women in Nuclear Network - Margarita Kalinina-Pohl; Zenobia S Homan; Olga Martin; Nataliia Klos; Adeline du Crest; Ina Grigalashvili; Mădălina Ștefanic; Şebnem Udum (International Journal of Nuclear Security, 2023)
This paper describes the establishment of a new professional network for women in nuclear that represents the interests of professionals in the Black Sea region. The paper examines the benefits of creating and sustaining professional networks for women, and it underlines the role of such networks in strengthening regional security culture during times of crisis using the Black Sea Women in Nuclear Network (BSWN) as a case study. In general, the network provides an interdisciplinary platform for professionals to promote gender equity and increase women’s leadership roles, as well as professional exchanges, mentoring, and training opportunities. More specifically, since its inception, the network has spearheaded several unique programs and initiatives. Many BSWN members currently work in challenging environments, which means they are especially adept at rapidly transforming problems into solutions. The network has provided concrete support to its community during the war in Ukraine and the earthquake in Türkiye and facilitated information-sharing on available resources and reliable news. With its own programs, the network provides a particular regional platform that complements other organizations’ efforts.
Keywords: women; DEI; gender equality; nuclear security; nuclear safety; nuclear security culture; professional networks